HUBUNGAN ASAS KEBEBASAN BERKONTRAK DAN ASAS ITIKAD BAIK PADA SAAT PRA KONTRAKTUAL DALAM HUKUM PERJANJIAN INDONESIA - , SA'IDA RUSDIANA, Taufiq El Rahman, S.H, M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this research is to assess whether the principle of objective good faith as defined in Article 1338 Paragraph (3) Civil Code could be applied at the pre-contractual time. This research also has aim to determine the form of restrictions on entry into force of the freedom of contract principle, especially if linked with the principle of good faith during the pre-contractual. In addition to examining how the correlation between these two principles are related to the balance principle in the agreement. It is a normative juridical research where the author examines the principles and doctrines relating to the subject matter in depth. The research was done by studying the documents to obtain secondary data. Data obtained from the research literature were then analyzed qualitatively with a descriptive presentation. The results showed that the principle of objective good faith as defined in Article 1338 Paragraph (3) Civil Code could be applied at the time of precontractual. Form of restrictions on entry into force of the freedom of contract principle, especially if linked with the good faith principle at the moment is in the form of pre-contractual agreements or forms that require certain formalities, restrictions include clauses that are contrary to the fairness or propriety and government intervention through legal tools made. Correlation of the freedom of contract principle relating to the balance principle in the agreement that is against the application of the freedom of contract principle which are positive will be able to create a balance position of the parties at the time of pre-contractual, otherwise the application of the freedom of contract principle which could cause unsteady negative balance in the pre-contractual. Application of the good faith principle could reduce the influence of an imbalance in the parties' bargaining positions at the time of pre contractual so that it could towards achieving a balanced agreement.